Determination of the viscoelastic properties of hydrogels based on polyethylene glycol diacrylate (PEG-DA) and human articular cartilage. (26th March 2009) - Gabler, Stefan; Stampfl, Jurgen; Koch, Thomas; Seidler, Sabine; Schuller, Georg; Redl, H.; Juras, Vladimir; Trattnig, Siegfried; Weidisch, Roland
In this work, a systematic study of the viscoelastic properties of hydrogels based on polyethylene glycol diacrylate (PEG-DA) is presented. In addition to artificial PEG-DA-based hydrogels, natural hydrogels in the form of human articular cartilage were examined. Specimens were (unconfined) compression tested under static and dynamic load. Besides this, instrumented indentation tests with different indenter geometries (cylindrical, spherical) and load ranges (macro- and nano-indentation) were carried out and relaxation tests for the determination of moduli and relaxation time were performed. Tensile tests completed the list of measurement techniques. The measured initial moduli of the evaluated hydrogels range from 104?107 Pa. Spherical indentation was used in testing human articular cartilage in phosphate buffered saline (PBS). Cartilage samples were measured shortly after explantation, being stored at room temperature. The influence of freezing and shock-freezing was evaluated. It turned out that freezing has a massive impact on sample properties, especially on the stress relaxation time and the ratio of initial to equilibrium modulus.